2016
DOI: 10.3389/fmars.2016.00256
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Leucine, Chitin, and Iron by Prokaryotic Groups during Spring Phytoplankton Blooms Induced by Natural Iron Fertilization off Kerguelen Island (Southern Ocean)

Abstract: Iron and carbon are essential for microbial heterotrophic activity, but the bioavailability of these elements is low in surface waters of the Southern Ocean. Whether the access to iron and carbon differs among phylogenetic groups of prokaryotes is barely known. To address this question we used iron (55 FeCl 3), and the carbon compounds chitin (3 H-Diacetylchitobiose) and leucine (3 H-leucine) as model substrates in combination with MICRO-CARD-FISH during spring phytoplankton blooms induced by natural iron fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 83 publications
(121 reference statements)
1
35
0
Order By: Relevance
“…Flavobacteria are known to be efficient degraders of complex polymers, such as polysaccharides, proteins or chitin, and tend to be less active than other bacterial groups in taking up simple sugars or amino acids González et al 2008;Straza et al 2010;Simon et al 2012;Wietz et al 2015;Fourquez et al 2016). These characteristics are supported by proteomic and genomic studies showing that Flavobacteria possess numerous genes involved in hydrolytic activities as well as high molecular weight compounds transporters such as TonB-dependent receptors, and comparatively low numbers of genes involved in the uptake of low molecular weight compounds (González et al 2008;Gómez-Pereira et al 2012;Fernández-Gómez et al 2013;Williams et al 2013).…”
Section: Ecology and Functional Traits Of Taxa Selected By Winter Watmentioning
confidence: 99%
“…Flavobacteria are known to be efficient degraders of complex polymers, such as polysaccharides, proteins or chitin, and tend to be less active than other bacterial groups in taking up simple sugars or amino acids González et al 2008;Straza et al 2010;Simon et al 2012;Wietz et al 2015;Fourquez et al 2016). These characteristics are supported by proteomic and genomic studies showing that Flavobacteria possess numerous genes involved in hydrolytic activities as well as high molecular weight compounds transporters such as TonB-dependent receptors, and comparatively low numbers of genes involved in the uptake of low molecular weight compounds (González et al 2008;Gómez-Pereira et al 2012;Fernández-Gómez et al 2013;Williams et al 2013).…”
Section: Ecology and Functional Traits Of Taxa Selected By Winter Watmentioning
confidence: 99%
“…For the normalization step, we therefore assumed that the above‐mentioned ratio derived from qPCR data equals the ratio of SAR11‐isocitrate lyase gene transcripts (metatranscriptome; RNA) to the number of SAR11 cell per L estimated by CARD‐FISH (as described in the study by Fourquez et al . ): qTiso/qCiso=mTiso/nCSAR11 where, for the purpose of this study, qT iso /qC iso is the ratio of SAR11‐isocitrate lyase gene transcripts L −1 (qT iso ) to SAR11‐isocitrate lyase gene copies L −1 (qC iso ) estimated by qPCR (Beier et al ., ), mT iso is the number of SAR11‐isocitrate lyase gene transcripts L −1 , and nC SAR11 is the SAR11 cells L −1 estimated by CARD‐FISH (Fourquez et al . )…”
Section: Methodsmentioning
confidence: 99%
“…The OTUs were corrected for copy numbers of 16S rRNA gene per cell per specific taxa obtained from the ribosomal RNA database (Stoddard et al ., ). Total cell numbers per bacterial group were then calculated with 16S rRNA gene relative proportions and counts from the Eub228‐I, ‐II and ‐II catalysed reporter deposition–fluorescence in situ hybridization (CARD‐FISH) probe from the same samples (data from the study by Fourquez et al ., , Supporting Information Table S6).…”
Section: Methodsmentioning
confidence: 99%
“…Although there is little experimental evidence about the capabilities of distinct bacterial populations to degrade polysaccharides in marine surface waters, some studies have shown the dominance of taxa belonging to the Gammaproteobacteria and/or Bacteroidetes groups in microcosms amended with starch, alginate or agarose (Simon et al, 2012;Wietz et al, 2015). By contrast, only members from the Bacteroidetes group seem to have a prominent role in the degradation of chitin (Wietz et al, 2015;Fourquez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the widely studied patterns of utilization of monomers at the single cell level, relatively few studies have examined macromolecule incorporation by specific marine microbes (Cottrell and Kirchman, 2000;Elifantz et al, 2005;Fourquez et al, 2016), documenting differences in incorporation at the phylum and class levels. To the best of our knowledge, the utilization of starch in natural communities has not yet been evaluated at a single-cell level.…”
Section: Introductionmentioning
confidence: 99%